A cross-sectional study of small mammals for tick-borne pathogen infection in northern Mongolia. Issue 1 (1st January 2018) - Pulscher, Laura A.; Moore, Thomas C.; Caddell, Luke; Sukhbaatar, Lkhagvatseren; von Fricken, Michael E.; Anderson, Benjamin D.; Gonchigoo, Battsetseg; Gray, Gregory C.
ABSTRACT: Background : Tick-borne pathogens (TBPs) are frequently studied in developed nations but are often neglected in emerging countries. In Mongolia, TBP research is especially sparse, with few research reports focusing upon human and domestic animal disease and tick ecology. However, little information exists on TBPs in small mammals. Methods : In this 2016 cross-sectional pilot study, we sought to uniquely study wildlife for TBPs. We live-trapped small mammals, and tested their whole blood, serum and ear biopsy samples for molecular or serological evidence of Borrelia spp., Rickettsia spp., and Anaplasma spp. /Ehrlichia spp. Results : Of 64 small mammals collected, 56.0%, 39.0% and 0.0% of animals were positive by molecular assays for Borrelia spp., Rickettsia spp., and Anaplasma spp. /Erhlicia spp., respectively. 41.9% were seropositive for A. phagocytophilum and 24.2% of animals were seropositive for Rickettsia rickettsii . Conclusion : This pilot data demonstrates evidence of a number of TBPs among small mammal populations in northern Mongolia and suggests the need to further investigate what role these mammals play in human and domestic animal disease.